CHEMICAL CONSTANTS OF SOME EDIBLE OILS WITHIN THE STATE OF ANDHRA PRADESH - N. MADHAVI,; T. DEVA SAROJA, (International Journal of Pharma and Bio Sciences, 2014)
The commercially available oil samples are analyzed for their Iodine, Saponification, Peroxide and Acid values. These values are subjected to statistical analysis by comparing with each other. The least Iodine value was identified for Coconut oil. Lower peroxide values were observed in the oils from Groundnut, Olive, Coconut and Rice bran. Sunflower oil exhibited the highest saponification value. Rice bran and Palm oil has the lowest Acid values. These properties help the chemist to opt for the suitable oil for household purposes and other requirements.